Echinococcosis in Liver - a case report (Journal of Dhaka Medical College, 2015)
The most common cause of hydatid disease in humans is infestation by the parasite Echinococcus granulousus. A 33 years old female patient with complaints of upper abdominal pain, discomfort, anorexia, nausea and loss of weight, was referred for ultrasound assessment of the whole of the abdomen. On ultrasound, her liver was enlarged in size. A fairly large cystic area measuring about (12 cm x 7.6 cm) having internal septations giving the appearance of cartwheel is noted in right lobe of liver. Intrahepatic biliary Channels and CBD were not dilated. Gall bladder, pancreas, spleen, both kidneys and other organs were found to be normal. No free fluid was seen in cul-de-sac. The patient was diagnosed as a case of echinococcosis in liver. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21548 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 223-224